Acetylsalicylic acid treatment reduce Fusarium rot development and neosolaniol accumulation in muskmelon fruit. (15th August 2019) - Xue, Huali; Bi, Yang; Sun, Yaxuan; Hussain, Raza; Wang, Hujun; Zhang, Shan; Zhang, Rui; Long, Haitao; Nan, Mina; Cheng, Xiaoyan; Alejandro, Calderóon-Urrea
Highlights: ASA inhibited the growth of Fusarium sulphureum. ASA disturbed the morphological and major cellular changes of F. sulphureum. ASA reduced Fusarium rot development in muskmelon fruits inoculated with F. sulphureum . ASA reduced neosolaniol accumulation in inoculated muskmelon fruits. ASA down-regulated Tri genes expressions involved in trichothecenes biosynthesis. Abstract: Fusarium rot of muskmelon is a common and frequently-occurring postharvest disease, which leads to quality deterioration and neosolaniol (NEO) contamination. New strategies to control postharvest decay and reduce NEO contamination are of paramount importance. The effects of acetylsalicylic acid (ASA) treatment on the growth of Fusarium sulphureum in vitro, and Fusarium rot development and NEO accumulation in fruits inoculated with F. sulphureum in vivo were investigated. The results showed that ASA inhibited the growth of F. sulphureum, evident morphological and major cellular changes were observed under the microscope. In vivo testing showed that 3.2 mg/mL ASA significantly suppressed Fusarium rot development and NEO accumulation after 6 and 8 d of pathogen inoculation. Meanwhile, Tri gene expressions involved in NEO biosynthesis were down-regulated after treatment. Taken together, ASA treatment not only reduced Fusarium rot development by inhibiting the growth of F. sulphureum, but decreased NEO accumulation by suppressing NEO biosynthesis pathway.